(untitled) (Research, Society and Development, 2021)
Exclusive breastfeeding up to six months of age and associated with adequate complementary feeding from six months to two years or more is the ideal feeding practice, capable of reducing infant mortality, promoting satisfactory growth and development and ensuring several protective factors for mothers and sons. However, the trade in food substitutes for breast milk, driven by marketing strategies, has been identified as one of the main factors associated with the low prevalence of breastfeeding in the world. In response, the World Health Organization published, in 1981, the International Code of Marketing of Food Substitutes for Breast Milk. In Brazil, the most important legal framework in defense of breastfeeding is the Brazilian Norm for the Marketing of Food for Infants and Early Childhood Children, nipples, pacifiers and baby bottles (NBCAL). The objective of this study was to identify NBCAL infractions found in pharmacies in the city of Belém. In addition to classifying the type of infraction, number of occurrences in pharmacies and georeferencing the locations for analysis of their characteristics. 145 pharmacies in 33 districts were evaluated. In 72% of the establishments some type of infraction was evidenced: 74 pharmacies offered discounts, 75 infringed the rules of spatial exposure and 48 committed both. The high rate of infringements found reinforces that, in Belém (PA), public policies to promote breastfeeding must necessarily include increased inspection of commercial establishments regarding compliance with NBCAL.